Arrhythmogenic Right Ventricular Cardiomyopathy: The Importance of Biventricular Strain in Risk-Stratification - Chua, Aileen Paula; Laenens, Dorien; Sarrazyn, Camille; Lopez-Santi, Maria Pilar; Nabeta, Takeru; Myagmardorj, Rinchyenkhand; Bootsma, Marianne; Barge-Schaapveld, Daniela Q.C.M.; Bax, Jeroen J.; Marsan, Nina Ajmone (Elsevier, 2025)
Despite arrhythmogenic right ventricular cardiomyopathy (ARVC) being predominantly a right ventricular (RV) disease, concomitant left ventricular (LV) involvement has been recognized. ARVC is diagnosed by the RV-centric 2010 Task Force Criteria(TFC) using routine echocardiography, but previous studies have suggested that strain imaging may be more sensitive to detect RV and LV dysfunction. No data however are available regarding the additional value of combining biventricular strain for risk stratification. This study aims to assess the prognostic value of both LV global longitudinal strain (GLS) and RV free wall strain (FWLS) in patients with ARVC. To accomplish this, 204 patients who met the TFC for the ARVC spectrum were included. Patients (age 41 § 17 years,55% men) were divided into impaired(n = 33), discordant (RV or LV impaired, n = 70), and normal (n = 101) strain groups based on a value of ≥18% for both ventricles. During a follow-up of 87 [24−136] months, 57 (28%) experienced the composite outcome of all-cause mortality, arrhythmic events, implantable cardioverter defibrillator therapy and heart failure events, and a significant difference in event-free survival was observed (p <0.001) between the 3 groups. In the multivariable analysis, the strain groups remained associated with outcomes (p = 0.014) after adjusting for age, sex, history of syncope and definite ARVC diagnosis. A subanalysis including only definite and borderline diagnosed ARVC confirmed that the strain groups were independently predictive of the endpoint (p = 0.023). In conclusion, biventricular involvement by strain analysis may help risk stratification in ARVC patients, with the worst outcomes of patients with both RV and LV impaired strain.